Wages and the Bargaining Regime in a Corporist Setting: The Netherlands - Joop Hartog; Edwin Leuven; Coen N. Teulings (Tinbergen Institute, 2000)
In a corporatist country, of which the Netherlands is an example, wages should not be distinguished by union membership status, but by the bargaining regime. Four bargaining regimes can be distinguished: (i) company level bargaining, (ii) industry level bargaining, (iii) mandatory extension of an industry agreement, and (iv) no collective bargaining. Acknowledging firms' bargaining regime, we find small differences between the four regimes, and certainly no distinction between “covered” and “uncovered” firms.
Keywords: J31; J51; 330; wages; collective bargaining; Verhandlungstheorie des Lohnes; Korporatismus; Theorie; Niederlande